2009
DOI: 10.1002/hyp.7331
|View full text |Cite
|
Sign up to set email alerts
|

The links between the categorised Southern Oscillation indicators and climate and hydrologic variables in Turkey

Abstract: Some previous global and regional studies have indicated teleconnection between the extreme phases of the Southern Oscillation (SO) and Turkish climate and hydrologic variables; however, they failed to suggest a strong correlation structure. In this study, categorised Southern Oscillation index (SOI) and Multivariate ENSO (El Nino Southern Oscillation) index (MEI) series were used to examine the far-reaching effects of the SO on temperature, precipitation and streamflow patterns in Turkey. These SO indicators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
0
15
1
Order By: Relevance
“…In Turkey, the relationships between large‐scale atmospheric circulations and climate and hydrologic variables (i.e., precipitation, temperature, and streamflow) have been well documented in the last two decades. A majority of these studies have attempted to evaluate the NAO and/or ENSO impacts (Kahya and Karabork, ; Karabork and Kahya, ; Turkes and Erlat, ; Kalayci et al ., ; Karabork et al ., ; Turkes and Erlat, ; Karabork et al ., ; Karabork and Kahya, ; Marti et al ., ). However, there have been a few studies conducted on the influences of the North Sea–Caspian Pattern (NCP) on Turkey hydroclimatological variables (Kutiel et al ., ; Kutiel and Turkes, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Turkey, the relationships between large‐scale atmospheric circulations and climate and hydrologic variables (i.e., precipitation, temperature, and streamflow) have been well documented in the last two decades. A majority of these studies have attempted to evaluate the NAO and/or ENSO impacts (Kahya and Karabork, ; Karabork and Kahya, ; Turkes and Erlat, ; Kalayci et al ., ; Karabork et al ., ; Turkes and Erlat, ; Karabork et al ., ; Karabork and Kahya, ; Marti et al ., ). However, there have been a few studies conducted on the influences of the North Sea–Caspian Pattern (NCP) on Turkey hydroclimatological variables (Kutiel et al ., ; Kutiel and Turkes, ).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, a number of studies have been undertaken to characterize variability and trends in observed records of streamflow and to establish linkages between the atmospheric circulation, climate and streamflow. These include studies in the USA (Fu et al , 2009), Canada (Zhang et al , 2001; Burn and Hag Elnur, 2002; Abdul Aziz and Burn, 2006; Burn, 2008), UK (Hannaford and Marsh, 2006, 2008), Europe (Mudelsee et al , 2003; Tu, 2006), Sweden (Lindstrom and Bergstrom, 2004), Switzerland (Birsan et al , 2005), the Amazon basin in Brazil (Marengo, 2009), Turkey (Karabörk and Kahya, 2009), Iran (Masih et al , 2010), South Korea (Bae et al , 2008) and Southern Africa (Fanta et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…ENSO variability affects the regional climate and hydrology of many parts of the world (KILADIS and DIAZ, 1989;CAYAN et al, 1999;SODEN, 2000), however the strength of its impact on Europe is still not unequivocally determined (ROPELEWSKI and HALPERT, 1987;FRAEDRICH and MÜ LLER, 1992;FRAEDRICH, 1994;DAI et al, 1997;MORON and WARD, 1998;CHIEW and MCMAHON, 2002;MARIOTTI et al, 2002;KARABÖ RK and KAHYA, 2009). The remainder of this section is organised as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of ENSO on drought generation in the Central-European country Hungary was found to exist but the strength of such a teleconnection was evaluated as rather low (PONGRÁ CZ et al, 2003) which might justify a weak ENSO-streamflow relationship in this part of Europe. KARABÖ RK and KAHYA (2009) reported a teleconnection between the Southern Oscillation and streamflow in selected Turkish rivers, including those in the European part of Turkey. KUNDZEWICZ et al (2005) also suspected that flood hazard might be associated with ENSO variability.…”
Section: Introductionmentioning
confidence: 99%